Pengembangan Komik Anak Untuk Meningkatkan Kemampuan Membaca Pemahaman Siswa Kelas III SD - Damanik, Dea Rahma; Devianty, Rina (Universitas Islam Lamongan, 2024)
The study aims to provide instructional materials, such as children's comics, to help students become more proficient readers. The four steps of the 4-D model used in this research are defined, designed, developed, and disseminated. It is a research and development (R&D) study. Student learning outcomes following the usage of comic media, teacher and student questionnaires, validation questions from media experts, and material experts are all used in the research data collection process. This research was conducted on 11 class III students at MIS Hubbul Wathon. The research results by media experts obtained 96% of the category (very valid), and the assessment by material experts was 91% of the category (very valid). In comparison, the assessment by teacher responses received a score of 98% in the category (very practical), and student responses received a score of 98% in the category (very practical). The use of comic media in learning impacts increasing reading comprehension skills by 0.6 or the medium category. Comic learning media is suitable for learning because it can improve students' reading comprehension.